Dynamical effects of sprints start on different starting blocks - Yu, L. -C.; Wu, Y. -L.; Yeh, M.-C.; Tsai, C. -L. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to examine the dynamical variables of sprint start in two different starting blocks setups. The ReacTime Personal Systems was used to record the Reaction Time (RT) and the Power of 20 teenaged sprinters (15 males and 5 females) in the sprint start. In addition, the Newtest Powertimer photocells were used to collect subjects` 0 to 10 metre (T10) performance after the sprint start. The variables were tested by the repeated measures one-way ANOVA by SPSS 19.0 statistical software at a .05 significant level. The results showed that there were better effects on the short starting block (SB) in power generation performance than the long starting block (LB). The athletes can apply short starting block and make adjustments and modifications based on their training conditions.